The effect of antifungal resistance development on the virulence of Candida species. Issue 1 (23rd March 2022) - Bohner, Flora; Papp, Csaba; Gácser, Attila
Abstract: In recent years, the relevance of diseases associated with fungal pathogens increased worldwide. Members of the Candida genus are responsible for the greatest number of fungal bloodstream infections every year. Epidemiological data consistently indicate a modest shift toward non-albicans species, albeit Candida albicans is still the most recognizable species within the genus. As a result, the number of clinically relevant pathogens has increased, and, despite their distinct pathogenicity features, the applicable antifungal agents remained the same. For bloodstream infections, only three classes of drugs are routinely used, namely polyenes, azoles and echinocandins. Antifungal resistance toward all three antifungal drug classes frequently occurs in clinical settings. Compared with the broad range of literature on virulence and antifungal resistance of Candida species separately, only a small portion of studies examined the effect of resistance on virulence. These studies found that resistance to polyenes and echinocandins concluded in significant decrease in the virulence in different Candida species. Meanwhile, in some cases, resistance to azole type antifungals resulted in increased virulence depending on the species and isolates. These findings underline the importance of studies aiming to dissect the connections of virulence and resistance in Candida species. Abstract : The authors discuss how the rising clinical relevance of fungal infections to the understanding of antifungal resistance development and its effects on the virulence attributes of pathogens could be highly beneficial, as it could lead to more efficient therapeutic practice.